2007
DOI: 10.1158/1055-9965.epi-07-0374
|View full text |Cite
|
Sign up to set email alerts
|

Intra-individual Variation of Plasma Adipokine Levels and Utility of Single Measurement of These Biomarkers in Population-Based Studies

Abstract: Adipokines, soluble mediators produced by adipocytes, may link adipose tissue to the inflammatory, metabolic, and immune dysregulation that characterize many obesity-related diseases. The stability of plasma adipokine levels within individuals, their seasonal variability, intercorrelations, and relationships to wellestablished measures of adiposity are incompletely defined. We measured levels of 12 adipokines [interleukin 1B (IL-1B), IL-6, IL-8, tumor necrosis factor-A (TNF-A), plasminogen activator inhibitor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
80
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 44 publications
10
80
2
Order By: Relevance
“…Furthermore, this method might provide much more meaningful information regarding short-term regulation of circulating hormone levels. Although plasma adiponectin levels do not vary markedly over longer periods of time in the absence of significant body weight changes (20), there may be a short-term biovariability. Short-term biovariability has been found to be twofold greater in healthy subjects than in those with the metabolic syndrome (21), and the present study has focused on healthy subjects.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, this method might provide much more meaningful information regarding short-term regulation of circulating hormone levels. Although plasma adiponectin levels do not vary markedly over longer periods of time in the absence of significant body weight changes (20), there may be a short-term biovariability. Short-term biovariability has been found to be twofold greater in healthy subjects than in those with the metabolic syndrome (21), and the present study has focused on healthy subjects.…”
Section: Discussionmentioning
confidence: 98%
“…However, several studies have provided evidence of a reasonable between‐to‐within person variability ratio (ICC) suggesting temporal stability for panels of cytokines 30, 31, 32, 33, 34, 35. Finally, blood cytokines are produced not only by those cell types considered to play pivotal roles in the immune system and in inflammatory responses, including lymphocytes, monocytes and mast cells but also by macrophages and, for some cytokines, also fibroblasts, neutrophils and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this analysis, the interassay CVs for leptin were 4.5% for low (mean, 5.3 ng/mL); 7.9% for medium (mean, 11.0 ng/mL); and 5.9% for high levels (mean, 26.1 ng/mL); for sOB-R the respective CVs were 10.0% (mean, 10.9 ng/mL); 9.7% (mean, 11.0 ng/mL); and 9.4% (mean, 27.2 ng/mL). In reproducibility studies reported intraclass correlation coefficients for leptin were 0.74, over 4 years in the Health Professionals Follow-up Study (33), 0.83, over 1 year in the Janus cohort study (10), 0.84 over 4 seasons in MONICA and V€ asterbotten Intervention Study (34), and for sOB-R, 0.82 over 3 years in the Nurses' Health Study (35).…”
Section: Blood Collection and Laboratory Proceduresmentioning
confidence: 99%